Personal Development Peculiarities on Gender Perspective in Georgia - Kharadze, Natalia; Gulua, Ekaterine (European Journal of Social Science Education and Research, 2025)
Receiving appropriate education and occupying a place in the labor market is not easy. The barriers that a person has to overcome can be solved systematically by personal development and joint efforts of universities or an organization. We must take any action that leads to success and act in spite of the fact that this action may not be a great pleasure. Everyone has aspirations. It is important for people to link these skills to the field of their activity. When you love your own job and you are prone to it, you have more chance of achieving success with less effort. Being successful is the need for any person, but not everyone can achieve it. People differ from each other by their goals, to what extent they are ready to overcome the barriers to achieving a goal, how they can survive problems, contradictions. Naturally, achieving a goal requires great work and support. Failures often happen while trying to succeed. At this time, it is necessary to overcome pessimism and it is important to develop optimism by analyzing the causes of the failure. ‘Hard work’ does not mean ‘effective work’. The most important thing is to use the resources wisely and achieve the goal by effective work. Today there are many methods to help people discover their abilities, with the help of this method they improve their communication skills, increase their labor productivity and achieve success by spending less energy. One of these methods is Augusto Boal’s method. What is young people’s attitude to personal development, how much support do they feel from the university and what expectations do they have from their organizations, how well are they determined, what is their attitude towards life - positive or negative; how can they deal with stress, develop creative thinking, develop leadership skills? - These issues have become an interesting topic for our laboratory, which are functioning at the Faculty of Economics and Business at Ivane Javakhishvili Tbilisi State University. The laboratory has conducted a number of studies, which have already been published in various magazines or at conferences. The studies focused on students' time budget, organizational culture and conflicts in an organization, as well as the assessment criteria for professors.
Keywords: Organization, Humane Resources Managment, Personal Development, Gender.